Exploring the metabolic signature of intermittent explosive disorder: Preliminary evidence and potential mechanisms for altered bilirubin metabolism - Jeffrey B. Schwimmer; Murray B. Stein; Emil F. Coccaro; Alejandro D. Meruelo (Comprehensive Psychoneuroendocrinology)
Intermittent Explosive Disorder (IED) is characterized by impulsive aggression and emotional dysregulation, yet its systemic biological underpinnings remain poorly understood. This study examined bilirubin metabolism and systemic biomarkers as indicators of metabolic vulnerability in individuals with IED. Laboratory data for total and indirect bilirubin and white blood cell (WBC) count were analyzed in individuals with IED and a demographically and clinically matched general population (GP) control group. A 10:1 nearest-neighbor propensity score matching procedure was used to balance covariates including age, sex, race, ethnicity, body mass index (BMI), and alcohol and tobacco use. Participants with hepatobiliary or inflammatory conditions were excluded to reduce heterogeneity and confounding. Group comparisons used unique individuals with biomarker values averaged across timepoints.Individuals with IED showed lower total and indirect bilirubin levels compared to matched controls, with a moderate effect size for indirect bilirubin (d = −0.37) and a small effect for total bilirubin (d = −0.10). WBC differences were minimal (d = −0.12). Linear mixed-effects models incorporating repeated measures yielded consistent results, though none of the group differences reached statistical significance, likely due to limited sample size in the IED group. Sensitivity analyses suggested bilirubin findings were more robust to unmeasured confounding than WBC.These results highlight a potential hepatobiliary or metabolic signature in IED, rather than a primary inflammatory process. Given the preliminary nature of the findings, absence of cytokine data, and limited statistical power, results should be interpreted cautiously and warrant replication in larger samples with broader inflammatory and lifestyle profiling.